GAP ANTARA DAS SOLLEN DAN DAS SEIN ILMU-ILMU KEAGAMAAN ISLAM: Perspektif Filsafat Ilmu - Yusuf Suyono (Jurnal Theologia, 2016)
Abstract: Since the Muslim Reformers launched the campaign of calling to return the glory of Islam back to Muslim people like what had been reached in classic era, the call came into nothing. The backwardness, ruin, and destruction in all aspects of life in Middle era could not have been completely overcome. The scientifical sphere which is hoped to be real means to reach the glory and get rid of these destructions,does not work as what has been hoped. Accordingly, nothing of what was mentioned by Thomas S. Kuhn as Shifting Paradigm happens, because the scientifical anomalies could not be overcome and in turn the crisis accumulates that lead to no scientifical revolution. In this case, Islamic sciences in general and Islamic religious sciences in particular do not develop. The religious sciences taught in Islamic University nowadays are those taught in classic era. The slogan of modern Islam “ the door of Ijtihad must be open ” changes that of middle era “ The door of Ijtihad must closed ” really be campaigned, but has no longer effect. Consequently, Islamic religious sciences have no relevance to their users. They taste very heavenly not worldly. That is what the writer means as the gap in Islamic sciences. Abstrak: Sejak para pemabaharu Muslim di abad 19 M mendengungkan ajakan untuk mengembalikan kejayaan Islam sebagaimana yang telah dicapai di era klasik, ajakan itu seperti belum menghasilkan apa yang diharapkan. Ke¬terpuruk¬an, keterbelakangan di berbagai bidang yang mereka sejak era pertengahan belum bisa sepenuhnya teratasi. Bidang keilmuan yang mestinya menjadi lokomotif dan garda depan untuk menggapai kejayaan yang bisa mengusir keterpurukan dan keterbelakangan tersebut, juga tidak berjalan sebagaimana mestinya. Pada gilirannya, tidak terjadi apa yang disebut oleh Thomas S. Kuhn sebagai Shifting Paradigm, karena anomali-anomali yang di dalamnya tidak bisa diatasi sehingga krisis menumpuk namun tidak terjadi revolusi ilmiah. Secara demikian rupa, sehingga ilmu-ilmu keislaman terutama ilmu agama menjadi mandeg. Ilmu-ilmu agama yang diajarkan di Perguruan Tinggi Agama Islam adalah juga masih yang digagas para pendahulu di era klasik. Semboyan era modern “ Pintu Ijtihad harus dibuka “ menggantikan semboyan era pertengahan “ Pintu Ijtihad Tertutup “ memang sudah dicanangkan, namun nuansanya Pintu Ijtihad itu masih terus tertutup. Akibatnya, ilmu-ilmu agama Islam seperti putus relevansi dengan masyarakat penggunanya. Ilmu-ilmu agama terasa melangit, padahal penggunanya ada di bumi. Itulah yang dimaksud dengan gap dalam ilmu-ilmu Islam.